Study on moral message pragmatic and aesthetic on the image for the young generation / Edy Tri Sulistyo and Liza Marziana Mohammad Noh - Tri Sulistyo, Edy; Mohammad Noh, Liza Marziana (Faculty of Art and Design, 2020)
This study intends to find the value of (moral) a philosophical-pedagogical. This point is an attempt to convey the fundamental and useful information for the younger generation and preservation of art and culture in Indonesia. Indonesia has the diversity and values of local wisdom (called the Java community is loaded with valuable local culture). Transformation of information in the form of values, especially the younger generation is perceived setbacks, therefore efforts to maintain the valuable values can be done in many ways. One way to study this is a delivery to the media image. Picture is for example an image signs, billboards, posters, banners, murals, etc.. The images are now presented / displayed in strategic places so that the people, especially the younger generation can read at any time. The hope is that the younger generation can implement in their daily lives.